The Na/K-ATPase role as a signal transducer in lung inflammation - Silva, Adriana Ribeiro; Souza e Souza, Kauê Franscisco Correa de; Souza, Thamires Bandeira De; Younes-Ibrahim, Mauricio; Burth, Patrícia; Castro Faria Neto, Hugo Caire de; Gonçalves-de-Albuquerque, Cassiano Felippe (Frontiers in Immunology, 2024)
Acute respiratory distress syndrome (ARDS) is marked by damage to the capillary endothelium and alveolar epithelium following edema formation and cell infiltration. Currently, there are no effective treatments for severe ARDS. Pathologies such as sepsis, pneumonia, fat embolism, and severe trauma may cause ARDS with respiratory failure. The primary mechanism of edema clearance is the epithelial cells' Na/K-ATPase (NKA) activity. NKA is an enzyme that maintains the electrochemical gradient and cell homeostasis by transporting Na+ and K+ ions across the cell membrane. Direct injury on alveolar cells or changes in ion transport caused by infections decreases the NKA activity, loosening tight junctions in epithelial cells and causing edema formation. In addition, NKA acts as a receptor triggering signal transduction in response to the binding of cardiac glycosides. The ouabain (a cardiac glycoside) and oleic acid induce lung injury by targeting NKA. Besides enzymatic inhibition, the NKA triggers intracellular signal transduction, fostering proinflammatory cytokines production and contributing to lung injury. Herein, we reviewed and discussed the crucial role of NKA in edema clearance, lung injury, and intracellular signaling pathway activation leading to lung inflammation, thus putting the NKA as a protagonist in lung injury pathology.